NGLY1 Deficiency: A Rare Genetic Disorder Unlocks Therapeutic Potential for Common Diseases. Issue 1 (3rd November 2022) - Walber, Simon; Partalidou, Georgia; Gerling‐Driessen, Ulla I. M.
Abstract: The enzyme catalysing the removal of N‐linked glycans from misfolded glycoproteins in the cytosol is an evolutionary well‐conserved glycanase called Peptide: N ‐glycanase (PNGase; NGLY1 in humans). NGLY1 hydrolyses the amide bond between an Asn and the proximal N ‐acetylglucosamine (GlcNAc) of the attached N‐glycan, thereby converting that particular Asn to Asp. Loss of NGLY1 due to heterozygous‐inactivating mutations cause a rare congenital disorder with a multisystemic clinical phenotype. Since the first case report in 2012, extensive research aiming at understanding the pathophysiology of the disease, revealed several crucial biological functions and pathways that involve NGLY1. Here, we highlight the research progress of the past decade. A special emphasis is given to the important role that NGLY1 plays in the transactivation of the transcription factor (NFE2L1; NRF1) that regulates many processes of cellular homeostasis, including proteasome bounce back and oxidative stress response. Abstract :